On some collusive and signaling equilibria in ascending auctions for multiple objects - Gian Luigi Albano; Fabrizio Germano; Stefano Lovo (Fondazione Eni Enrico Mattei (FEEM), 2001)
We consider two ascending auctions and show that many of the (unwanted) collusive or signaling equilibria studied in the literature in the framework of the SEAMO (simultaneous English auction for multiple objects) don't have a counterpart in the JAMO (Japanese auction for multiple objects). We show however that certain retaliatory equilibria do exist in both auctions.
Keywords: C72; D44; 330; Multi-unit auctions; ascending auctions; FCC auctions; Auktionstheorie; Signalling; Kartell; Theorie